A microquasar model applied to unidentified gamma-ray sources - Bosch-Ramon, V. (2006)
Among unidentified gamma-ray sources in the galactic plane, there are some that present significant variability and have been proposed to be high-mass microquasars. To deepen the study of the possible association between variable low galactic latitude gamma-ray sources and microquasars, we have applied a leptonic jet model based on the microquasar scenario that reproduces the gamma-ray spectrum of three unidentified gamma-ray sources, 3EG J1735-1500, 3EG J1828+0142 and GRO J1411-64, and is consistent with the observational constraints at lower energies. We conclude that if these sources were generated by microquasars, the particle acceleration processes could not be as efficient as in other objects of this type that present harder gamma-ray spectra. Moreover, the dominant mechanism of high-energy emission should be synchrotron self-Compton (SSC) scattering, and the radio jets may only be observed at low frequencies. For each particular case, further predictions of jet physical conditions and variability generation mechanisms have been made in the context of the model. Although there might be other candidates able to explain the emission coming from these sources, microquasars cannot be excluded as counterparts. Observations performed by the next generation of gamma-ray instruments, like GLAST, are required to test the proposed model.